H.264 Compression Delivers More With Less - Freschi, Cynthia (Security, 2008)
First of all, the H.264 compression standard is not new. It was ratified by the joint MPEG/VCEG (Video Coding Experts Group) committee in 2003 as an extension of MPEG4, and was named MPEG4 Part 10 - although it is more generally known as H.264 AVC (Advanced Video Codec). The new compression algorithm was initially used most commonly in communication applications such as videoconferencing and was then subsequently adopted by the broadcast and computer industries. Essentially, H.264 compression technology compares a frame of video (R - reference frame) to the preceding coded frame (I - index frame) and then codes only the differences in the R frame. It continues doing this until a new I frame refreshes the scene. Think of a video surveillance camera focused on a gaming table wherein the green felt tabletop does not change but there is movement of the cards and motion by the dealer and the players. The camera would only process the changes in the frame; namely the movement of the cards and the motion of the individuals.